New mechanistic insights into macrophage extracellular trap formation induced by a parasitic nematode, Strongyloides stercoralis - Zhou, Taoxun; Zhang, Bingying; Zhu, Runxin; Wang, Chunqun; Liu, Hui; Gupta, Nishith; Hu, Min (Frontiers in Immunology, 2025)
Macrophages execute host defense against pathogens by releasing extracellular traps (METs) composed of DNA meshwork and antimicrobial proteins. Although MET-mediated pathogen immobilization is well documented, the induction mechanisms of MET generation by helminth parasites remain elusive. Here, we demonstrate that Strongyloides stercoralis larvae induce rapid chromatin extrusion in murine macrophages. Unlike neutrophil extracellular trap (NET) formation, MET formation does not require NADPH oxidase and exhibits distinct ultrastructural characteristics, including endoplasmic reticulum vesiculation, perinuclear space dilation, and inner nuclear membrane budding. Phosphoproteomic analysis revealed that MET formation is coordinately regulated by ERK and AKT signaling, F-actin cytoskeletal remodeling, histone acetylation, and phosphorylation of nuclear envelope (NE) proteins. Specifically, we show that protein kinase C zeta isoform (PKCζ)-mediated lamin A/C phosphorylation drives the NE budding and subsequent DNA expulsion. This work represents the first systematic delineation of the cellular dynamics and molecular machinery underlying MET formation, providing new insights into macrophage-directed anti-helminth immunity.